INFLUENCE OF ABILITY MATHEMATICS LITERACY AND MOTIVATION TO LEARN MATHEMATICS OF STUDENT TO ABILITY OF PROBLEM SOLVING MATHEMATICS ON SOCIAL ARITHMETIC - Aldila Maysarah Ayusari (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of mathematical literacy ability and motivation to learn mathematics on student problem solving abilities. The type of research used is non experiment with research design is survey, where the subjects used are students of class VII I SMP Negeri 4 Tulungagung which amounted to 31 students. Instrument used in this research is motivation questionnaire, observation sheet problem solving ability and script about ability of mathematics literacy. Data collection methods used are test methods, questionnaires and observations. Data analysis technique used is with normality test, multiple regression test, correlation test, and significance test. Based on data analysis, it is known that there is an influence of mathematical literacy ability and student learning motivation motivation (X1 and X2) on math problem solving ability (Y) on social grade arithmetic class VII I SMP N 4 Tulungagung.